КОНЦЕПЦІЯ ВИПУСКНОЇ КВАЛІФІКАЦІЙНОЇ РОБОТИ У ПОЗАШКІЛЬНОМУ НАВЧАЛЬНОМУ ЗАКЛАДІ ЯК ЧИННИК ФОРМУВАННЯ ОСОБИСТІСНИХ ЯКОСТЕЙ ЛЮДИНИ ШФОРМАЦШНОГО СУСПІЛЬСТВА (Педагогіка вищої та середньої школи, 2007)
The article is devoted to determination of role of qualifying final work in out-of-school educational establishment as mechanism of socialization of child that the acquisitions to them the personalities socially claimed qualities. On the basis of connection of results of achievements of researches in area of pedagogical psychologists, pedagogic and sociology, an author determines the educational and educating aims of teacher in the process of organization of student at writing of final work.